EDUKASI SADAR BENCANA MELALUI SOSIALISASI KEBENCANAAN SEBAGAI UPAYA PENINGKATAN PENGETAHUAN SISWA TERHADAP MITIGASI BENCANA - Pahleviannur, Muhammad Rizal (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
Indonesia is a country that has a high level of vulnerability to natural disasters. Based on the disaster index of risk, Central Java Province is one of the provinces that experienced the most disasters in Indonesia. Community preparedness efforts towards disasters are still considered weak, as evidenced by a large number of fatalities, property losses, and deaths. Children are classified as vulnerable to disaster management efforts and therefore require special efforts to increase knowledge about disaster mitigation. This study aims to increase students knowledge of disaster mitigation through disaster preparedness socialization activities to realize disaster resilient schools. This research is one form of community service through socialization activities with a qualitative approach. The result of the study shows that the level of students knowledge of disaster mitigation still needs for improving more. Low knowledge can increase the number of casualties resulting from disasters. The solution offered by researchers is conducting disaster awareness education activities through disaster socialization. It is expected that follow up actions such as maintenance and supervision as controls with the aim of such activities have the optimal result to increase students knowledge of disaster mitigation and the realization of disaster resilient schools.